2012
DOI: 10.1097/yco.0b013e32834de48a
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in the treatment of prolonged grief

Abstract: Prolonged grief, a pattern of persistent and elevated distress following a loss, is increasingly recognized as an independent form of psychopathology that is responsive to treatment. Therapies that employ cognitive-behavioral techniques are efficacious in ameliorating the symptoms of prolonged grief and should be more widely used. However, grief therapy should not be deployed as a blanket intervention for all grievers. Antidepressant medication may serve a useful adjunctive role in grief therapy completion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…Instead, interventions, such as grief therapy or psychotherapy, should be targeted to those in need. [53][54][55] Three levels of supportive interventions in grief have been suggested in a review of efficacy of intervention programs. 56 In primary preventive interventions, support is offered to all bereaved, however, there is no clear evidence about the effectiveness of this approach.…”
Section: Support In Bereavementmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, interventions, such as grief therapy or psychotherapy, should be targeted to those in need. [53][54][55] Three levels of supportive interventions in grief have been suggested in a review of efficacy of intervention programs. 56 In primary preventive interventions, support is offered to all bereaved, however, there is no clear evidence about the effectiveness of this approach.…”
Section: Support In Bereavementmentioning
confidence: 99%
“…As argued earlier in this thesis, all individuals are unique, [53][54][55] and, to understand how different factors affect the bereavement outcome for an individual, you must look at the conditions for that specific individual. It could be suggested that young adults may benefit from supportive interventions that are based on their risk and protective factors, which has previously been indicated as an appropriate approach for interventions to children with a seriously ill parent.…”
Section: Risk and Protective Factorsmentioning
confidence: 99%
“…By contrast, resilient people tended to experience their support network as more willing to listen to their concerns, had a greater willingness to rely on others when needed, and reported less worry about the availability of close others and lower levels of loneliness. On balance, these findings paint a portrait of psychological health among resilient bereaved people and underscore that prolonged grief is a debilitating syndrome that is appropriate for clinical intervention (Mancini, Griffin, & Bonanno, ).…”
Section: Resultsmentioning
confidence: 91%
“…For clinical purposes, in recent years, the concept of PG-or the closely related prolonged grief disorder (PGD)-has become the particular focus of researchers and therapists (Boelen and Prigerson, 2007;Goldsmith et al, 2008;Maccallum and Bryant, 2013;Maercker and Lalor, 2012;Mancini et al, 2012;Prigerson et al, 2009). In the process of preparing the 11th version of the International Classification of Diseases (ICD-11) by the World Health Organization, a revised concept of PGD was proposed as a separate disorder belonging to the new category of "disorders specifically associated with stress," next to posttraumatic stress disorder and adjustment disorder (Maercker et al, 2013).…”
mentioning
confidence: 99%